6721 Short-Term Responses of Serum 25-Hydroxyvitamin D to Weekly Calcifediol or Cholecalciferol in Healthy Subjects - Caldeira, R B; Nunes, A S; Cazzetta, F Z; Medeiros, M S; Oliveira, L B; Bandeira, M P; Bandeira, F F (Journal of the Endocrine Society, 2024)
Abstract Disclosure: R.B. Caldeira: None. A.S. Nunes: None. F.Z. Cazzetta: None. M.S. Medeiros: None. L.B. Oliveira: None. M.P. Bandeira: None. F.F. Bandeira: None. Introduction: Recent studies have shown that oral calcifediol (CAL) induces faster serum 25-hydroxyvitamin D (25OHD) increases than cholecalciferol (CHO) as demonstrated in some studies on SARS-Cov2 infection. It is hypothesized that this rapid elevation is due to the unique mode of intestinal absorption of CAL to the portal vein system in comparison with CHO which is absorbed mainly by the lymphatic route. Data on weekly administration of calcifediol are still scarce. The aim of the present study was to compare serum 25OHD responses in the short term (30 days) to weekly doses of CAL or CHO in healthy subjects. Methods and Results: We studied 35 subjects (34% men, mean age 24.6 ± 4.6 years, BMI 22.9 ± 2.9 kg/m², waist circumference 74.7 ± 6.5 cm, SBP 111.1 ± 12.7 mmHg, and DBP 73.1 ± 9.1 mmHg) who were randomized to receive weekly oral CAL 70 mcg (18 subjects) or CHO 350 mcg (14,000 IU, 17 subjects). Doses were chosen based on the 2000 IU/day potency equivalence. Patients were matched for age, gender, BMI, and BP. They were contacted weekly to confirm medication adherence. Serum 25OHD concentrations were measured before administration of both agents and 24 hours after the last dose, using an immunochemiluminescent assay (Abbott Diagnostics, Lake Forest, IL, USA) with a detection range from 4.9 to 151.3 ng/ml. At baseline serum 25OHD was 32.1 ±8.8 vs 33.1 ± 6.6 in CAL and CHO groups respectively (p=0.691). In CAL group 8 subjects had serum 25 OHD < 30 ng/mL (1 subject had 14.7 ng/mL) and in the CHO none had serum 25OHD below 20 ng/mL and 5 subjects had levels between 20 and 30 ng/mL. After 1 month, serum 25OHD levels rose significantly 3.3 times more with CAL than with CHO (+29.61 ± 7.39 ng/mL vs. 9.00 ± 3.50 ng/mL; p < 0.001). In CHO group one subject remained with 25OHD below 30 ng/mL after the intervention. Conclusion: We found a rapid and robust elevation of serum 25OHD levels with CAL compared to CHO at similar potency doses. This may have clinical implications for conditions in which there is a need for immediate availability of 25OHD to peripheral tissues. Presentation: 6/2/2024